2017
DOI: 10.7150/ijbs.17696
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Estradiol on the Growth Plate Chondrocytes of Limb and Spine from Postnatal Mice in vitro: The Role of Estrogen-Receptor and Estradiol Concentration

Abstract: Objectives: Skeletal development is a complex process. Little is known about the different response of limb or spine growth plate chondrocytes (LGP or SGP) to the estrogen level and the role of estrogen receptor (ER) during postnatal stage.Methods: LGP and SGP chondrocytes were isolated from 50 one-week mice and treated with different concentrations of 17β-estradiol. Cell viability was measured by cell counting kit-8 (CCK-8). The expression of collagen II and X were evaluated by real-time PCR and Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
(40 reference statements)
0
11
1
Order By: Relevance
“…Both ERα and ERβ appeared to be involved in pain transmission and modulation but might be acting at distinct levels of the pain pathways [ 28 ]. However, the substantial contribution of estrogen to the IVD related pain remains unclear, although hormonal factors are generally associated with chronic musculoskeletal pain in women [ 29 34 ]. Osteoarthritis (OA) is also more common in women after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Both ERα and ERβ appeared to be involved in pain transmission and modulation but might be acting at distinct levels of the pain pathways [ 28 ]. However, the substantial contribution of estrogen to the IVD related pain remains unclear, although hormonal factors are generally associated with chronic musculoskeletal pain in women [ 29 34 ]. Osteoarthritis (OA) is also more common in women after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus-producing HepG2 cells were cultured in DMEM supplemented with 2 mM L -glutamine, 50 U mL −1 penicillin and 10% fetal bovine serum at 37°C in a 5% CO 2 atmosphere (Hong et al, 2013 ). The cytotoxicity of the lettuce leaf extracts toward HepG2 cells was assessed using the CCK-8 assay, as described by Shi et al ( 2017 ). Cell viability (%) was calculated as (OD450 (sample) – OD450 (blank) )/(OD (mock) – OD450 (blank) ).…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 cells were seeded at 5,000 cells/well in 96-well plates in 100 μL media, cultured for 24 h, incubated with 400 μM H 2 O 2 containing 1 μL of lettuce leaf extract or an equivalent volume of media (mock) or H 2 O 2 (400 μM H 2 O 2 solution plus 1 μL medium) as control treatments for 24 h, and cell viability was assessed using the CCK-8 assay as described by Shi et al ( 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The apparent antagonism of ER activity by QBA in these experiments could have been due to the high concentration of estradiol used or its combination with QBA, since the QBA-alone data indicated that QBA was an ER agonist. Such circumstances are possible because circulating levels of estradiol are typically in the picomolar range [ 48 , 49 ], and high agonist concentrations can result in inverted, U-shaped concentration-response curves [ 50 , 51 ]. Similarly, as reported here, our in vitro experiments of QBA effects on neurite extension and on mitochondrial health after hypoxia challenge showed that higher concentrations are not always better.…”
Section: Discussionmentioning
confidence: 99%